Dietary zinc addition influenced zinc and lipid deposition in the fore- and mid-intestine of juvenile yellow catfish Pelteobagrus fulvidraco. Issue 8 (26th September 2017) - Chen, Guang-Hui; Hogstrand, Christer; Luo, Zhi; Zhang, Dian-Guang; Ling, Shi-Cheng; Wu, Kun
Abstract: The present study explored the mechanisms of dietary Zn influencing Zn and lipid deposition in the fore- and mid- intestine in yellow catfish Pelteobagrus fulvidraco, and investigated whether the mechanism was intestinal-region dependent. For this purpose, yellow catfish were fed three diets containing Zn levels of 8·83, 19·20 and 146·65 mg Zn/kg, respectively. Growth performance, intestinal TAG and Zn contents as well as activities and mRNA expression of enzymes and genes involved in Zn transport and lipid metabolism in the fore- and mid-intestine were analysed. Dietary Zn increased Zn accumulation as well as activities of Cu-, Zn-superoxide dismutase and ATPase in the fore- and mid-intestine. In the fore-intestine, dietary Zn up-regulated mRNA levels of ZnT1, ZnT5, ZnT7, metallothionein (MT) and metal response element-binding transcription factor-1 (MTF-1), but down-regulated mRNA levels of ZIP4 and ZIP5. In the mid-intestine, dietary Zn up-regulated mRNA levels of ZnT1, ZnT5, ZnT7, MT and MTF-1, but down-regulated mRNA levels of ZIP4 and ZIP5. Dietary Zn reduced TAG content, down-regulated activities of 6-phosphogluconate dehydrogenase (6PGD), glucose-6-phosphate dehydrogenase (G6PD), malic enzyme (ME) and fatty acid synthase (FAS) activities, and reduced mRNA levels of 6PGD, G6PD, FAS, PPAR γ and sterol-regulator element-binding protein (SREBP-1), but up-regulated mRNA levels of carnitine palmitoyltransferase IA, hormone-sensitive lipase (HSLa), adipose TAG lipase (ATGL) and PPAR α in the fore-intestine. In the mid-intestine, dietary Zn reduced TAG content, activities of G6PD, ME, isocitrate dehydrogenase and FAS, down-regulated mRNA levels of 6PGD, G6PD, FAS, acetyl-CoA carboxylase a, PPAR γ and SREBP-1, but up-regulated mRNA expression of HSLa, ATGL and PPAR γ . The reduction in TAG content following Zn addition was attributable to reduced lipogenesis and increased lipolysis, and similar regulatory mechanisms were observed between the fore- and mid-intestine.